Effects of pyrolysis conditions and biomass properties on leachability and recyclability of inorganic nutrients in biochars produced from mallee biomass pyrolysis - Kong, Zhaoying (Curtin University, 2014)
Using biochar as a soil amendment agent can recycle a majority of inherent inorganic nutrients in biomass to the soil, largely enhancing the overall sustainability of pyrolysis technology. This work investigates the effects of pyrolysis conditions and biomass properties on the leachability and recyclability of nutrients in mallee biochars. Understanding the relationships between biochar preparation conditions and biochar nutrients recyclability will aid the optimisation of suitable conditions to produce biochar with excellent leachability.